The Role of Supplementary Retirement Savings in Reducing the Pension Gap in Poland - Jedynak, Tomasz (Economic and Environmental Studies, 2020)
The main aim of the study is to identify the size of the pension gap in Poland and to estimate the level of supplementary savings needed to cover it. The issue of pension system income adequacy is first discussed, and the forecasted and targeted levels of replacement rates in Poland are indicated. Next, the basic parameters determining the pension gap are defined and the size of the gap is analyzed. The amount of savings needed to cover the pension gap is then computed. How changes in the values of particular parameters influence the amount of monthly savings needed to cover the individual pension gap is discussed. As a result of the studies, it was determined that the size of the future pension gap for the average worker in Poland is ca. 15-25% of his salary. To cover this gap, it is necessary to contribute additional funds to one’s retirement savings during the course of a professional career. Finally, the multitude of assumptions involved and the long horizon of the calculations make it impossible to precisely determine the amount of monthly savings needed to finance the pension gap.